2009
DOI: 10.1109/tsm.2009.2024872
|View full text |Cite
|
Sign up to set email alerts
|

Onset of Material Alterations Due to Laser-Induced Plasma Exposure in Nanofilms Deposited on Photomasks

Abstract: Damage-free removal of sub-100 nm particles from photomasks with deposited nanofilms is a challenge in lithography. Laser-induced plasma (LIP) is an emerging noncontact, chemical-free, dry, and selective nanoparticle removal technique. Investigation of the onset of material alterations on bonded nanofilms for optimizing LIP particle removal process is the objective of this paper. Shockwave thermomechanical excitation and radiation heating from the plasma core are major potential sources of damage. Computationa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2011
2011
2012
2012

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 38 publications
1
5
0
Order By: Relevance
“…The static yield stress of chrome film is 362 MPa. However, considering the experimental studies and the dynamic strain rate factor reported in [18], there would not be any damage at a threshold firing distance of 2.5 mm.…”
Section: Results Of Transient Thermoelastic Analysismentioning
confidence: 97%
“…The static yield stress of chrome film is 362 MPa. However, considering the experimental studies and the dynamic strain rate factor reported in [18], there would not be any damage at a threshold firing distance of 2.5 mm.…”
Section: Results Of Transient Thermoelastic Analysismentioning
confidence: 97%
“…Discoloration is the least damaging of the material alteration modes observed. LIP exposure on these EUVL mask blank samples, when compared to that on photomask blank samples [23], indicate more severe cracking on photomasks. In the experiments reported in is paper, no material alteration or damage was observed for LIP application at a clearance distance of d = 3.6 mm for n = 200 shots on the EUVL mask blank sample consisting of a 2.5-nm Ru on 105 nm of Mo/Si MLs on a LTEM substrate.…”
Section: Lip Experiments For Materialsmentioning
confidence: 81%
“…Previously, LIP shockwaves and the radiation intensity heating were characterized to determine whether material alterations would be initiated on EUVL masks. Utilizing transient pressure transducers, LIP shockwave pressure was acquired, shockwave temperature was estimated (from gas dynamics relationships and the measured pressure levels) [21], and the radiation intensity was approximated from measured radiation energy (utilizing a volume absorber-type radiant power meter) [22], [23]. A finite element (FE) analysis was conducted by using these loading conditions on thin films and obtaining the resultant stresses and surface temperature on the EUVL mask.…”
Section: Experimental Setup Materials and Proceduresmentioning
confidence: 99%
See 2 more Smart Citations